MG-135 Metabolic diet app suite: Digital medicine to support families with inborn errors of metabolism. (4th December 2015) - van Karnebeek, Clara DM; Ho, G; Houben, RFA; Joa, J; Ueda, K
Abstract : Background: Diets for inborn errors of metabolism (IEMs) are known to be burdensome, with lack of nutrient information often leading to compliancy issues, one-sided nutrition and frustration for children and families. Digital technologies provide the opportunity to develop Metabolic Diet Applications for handheld devices which can help families overcome these problems. Objective: We aimed to develop Applications comprising nutrient information with options for tracking and exporting food records, to facilitate therapeutic compliance for IEM patients on diets. Methods and results: Using Metabolic Pro Database we designed the 1st ever Metabolic Diet Apps Suite tailored to more than 15 different IEMs. Login to the App is personal. Features of each App include: relevant nutrient listing per food item, calculation tracking of food/nutrient intake, summary of food records with graphs, own recipes, and the possibility to export the food records as PDFs. We have performed a study on user friendliness; data was used to improve the Apps, to be launched summer 2014. Discussion: The Metabolic Diet App suite enhances personalised treatment of IEMs via digital medicine. Especially for adolescents the Apps will be attractive tools, allowing them to better understand and control their disease. Change in adherence will be evaluated.